Parental educational level and children's IQ scores : the relationship between educational level and children's cognitive functioning. - Byrne, Melani (My University, 2014)
The Relationship between Parental Educational Level and Children’s Cognitive Functioning This study investigated the relationship between a child’s measured intelligence and the educational level of that child’s mother and/or father. Correlations between parental educational level and children’s cognitive functioning as measured by a conventional South African intelligence scale, were examined. The instrument used to measure the children’s cognitive functioning in this study was the Senior South African Individual Scale-Revised (SSAIS-R). The children’s scaled scores were obtained from existing results on the SSAISR. Parental educational levels were obtained from existing intake questionnaires, which parents completed before their children were assessed on the SSAIS-R at the Centre for Psychological Services and Career Development (PsyCaD). Correlational analysis was used to investigate the relationship between the two variables of interest. The sample consisted of 23 cases. All of the children were aged between 8 and 10, spoke either English or Afrikaans as a first language, and belonged to the White, Indian or Coloured population groups. The results indicated that maternal level of education was positively and moderately correlated with children’s cognitive functioning. Paternal educational level and children’s cognitive functioning were found to have no correlation or to be inversely correlated. The correlation results between paternal level of education and children’s cognitive functioning should be interpreted with caution since the sample size was very small. Thus, the results are not statistically significant.
Keywords: Parental educational level; Children's cognitive functioning; Intelligence measures; SSAIS-R